If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5y+9=(-9-3y)
We move all terms to the left:
5y+9-((-9-3y))=0
We add all the numbers together, and all the variables
5y-((-3y-9))+9=0
We calculate terms in parentheses: -((-3y-9)), so:We get rid of parentheses
(-3y-9)
We get rid of parentheses
-3y-9
Back to the equation:
-(-3y-9)
5y+3y+9+9=0
We add all the numbers together, and all the variables
8y+18=0
We move all terms containing y to the left, all other terms to the right
8y=-18
y=-18/8
y=-2+1/4
| -3t^2+12t+36=0 | | 8/3d+4/3d=2 | | .75x-7=2.80 | | 1.21x+11.87=x+12.50 | | 0.006(9-k)+0.04(k-4)=1 | | 0.006(9−k)+0.04(k−4)=10.006(9-k)+0.04(k-4)=1 | | 11+3x=-14 | | x-16=360 | | x+16=360 | | 0.3(x+1632)=726 | | 32x-5)=2x+5 | | 2^{3x+1}=5 | | 5x+(-12x+24)=11 | | n–4=-12 | | X.x+4=-1.5x-21 | | 8=3o-1 | | (x+2)/3-40=-37 | | (x-8)/5+3=7 | | 3x+9=-80 | | 39.99+1.25x=25.99+1.75x | | -30-3z-z=48+2z | | -30-3z-z=48=2z | | 0.11x+0.6(x-4)=0.01(4x-2) | | 12+8y+y=2y+48=4y | | {x-2}{3}-5=-3 | | 2+16x-36=0 | | 1.3x+14=0.5x+14 | | 6x+4=-7x+134 | | (-3)+x=12 | | 96=8c=20-12c | | x+(-2)=35 | | x-2/3-5=-3 |